Interpretive framework for analyzing lean implementation using ISM and IRP modeling. Issue 9 (29th November 2018) - Chaple, Anup Prabhakarrao; Narkhede, Balkrishna Eknath; Akarte, Milind M.; Raut, Rakesh
Abstract : Purpose: Firms have been adopting lean manufacturing to improve their business performances. However, they are facing failures or less success in implementation, mainly due to lack of understanding in relating the lean practices (LPs) from the required performance measures perspective. In view of the lack of research and the importance of understanding them, the purpose of this paper is to prioritize LPs. Design/methodology/approach: As LPs are scattered in the literature and a variety of performance measures are used, an extensive literature review is first carried out to identify the LPs and performance measures. The blend of interpretive structural modeling and interpretive ranking process interpretive tools is adopted in establishing the contextual relationship among LPs and then ranking them based on the performance measures. A three-dimensional priority matrix is proposed for better explanation of the results. Findings: The proposed framework can help firms better understand LPs and their levels of importance in lean implementation. Research limitations/implications: The involvement of lean experts may produce some bias in evaluating the LPs. Practical implications: The proposed framework can help practitioners to develop an industry-specific road-map for the result-oriented LP implementation. Based on the area of performance to be improved, practitioners can prioritize LPs for implementation. Originality/value: This is the first study that provides a comprehensive review of LPs available in the literature and prioritizes them in accordance with performance with interpretive tools.